BRIDGING WELFARE-BASED EDUCATION BETWEEN FINLAND AND INDONESIA: TEACHERS’ PERCEPTIONS, EXPERIENCES, AND READINESS IN THE ERA OF MERDEKA BELAJAR - Bayu Marheta; Iwan Jazadi; I.G.A. Widari (GLOBAL: Education Language and Humanity Journal, 2025)
This study investigates Indonesian teachers’ perceptions, experiences, and readiness in implementing welfare-based teaching strategies inspired by the Finnish educational model and contextualized through Ki Hajar Dewantara’s philosophy. Using a qualitative multiple case study approach, five teachers from junior and senior high schools in West Nusa Tenggara and Java participated through questionnaires and semi-structured interviews. Thematic analysis revealed three key findings: (1) teachers conceptually recognize the importance of welfare in fostering emotional safety, autonomy, and motivation; (2) some welfare-oriented practices, such as brain breaks and student-friendly interactions, have been partially adopted, but teacher self-care remains neglected; and (3) readiness to fully implement welfare-based pedagogy is constrained by structural barriers, including policy pressures, heavy curriculum demands, and limited institutional support. These findings underscore the gap between aspirational reforms like Merdeka Belajar and the practical realities of classroom implementation. To achieve transformative change, policies must embed teacher well-being, curriculum flexibility, and localized pedagogical support. This study contributes actionable insights for aligning global best practices with Indonesia’s educational reform agenda.